Long-term benefits and performance of dams proceedings of the 13th conference of the British Dam Society held at the University of Kent, Canterbury, UK from 22 to 26 June 2004 - Hewlett, Henry (Thomas Telford, 2004)
Presents proceedings the 13th Conference of the British Dam Society held at the University of Kent, June 2004. These papers include discussion on the benefits that reservoirs can provide in terms of water supply and recreation, the environmental impact they can have, and the use of geomembranes to provide water tightness.